Kinetics of the Reaction Between Urokinase and an Inhibitor of Fibrinolysis from Placental Tissue - Christensen, Ulla; Holmberg, L; Bladh, B; Åstedt, B (Thrombosis and Haemostasis, 1982)
The interaction of urokinase (EC 3.4.21.31) and a protein proteinase inhibitor of fibrinolysis partially purified from placental tissue, which inhibits urokinase but not plasmin, was investigated. The preparations of the inhibitor contained no other known proteinase inhibitors. It was found that a 1:1 complex is formed and that the reaction proceeds as a second order, one step process, the association rate constant of which is 4.5 106 M−1 S−1 at pH 8.4, 37° C and 3.0 106 M−1 S−1 at pH 7.3, 37° C. The binding is very tight, the dissociation constant of the inhibitor-urokinase complex was estimated to be Ki≦10−11 M.
Keywords: Placental inhibitor of fibrinolysis; Urokinase; Reaction kinetics